Influence of B-site cations ordering on magnetization and dielectric relaxations in Li–Ni spinel ferrites. Issue 16 (15th August 2021) - Manzoor, Alina; Khan, Muhammad Azhar; Shahzad, Aamir; Al-Muhimeed, Tahani I.; AlObaid, Abeer A.; Albalawi, Hind; Afzal, Amir Muhammad; Kashif, Muhammad; Tahir, Sofia; Munir, Tariq
Abstract: Ho-substituted Li–Ni ferrites with composition L i1.2 Ni0.4 Hox Fe2- x O4 ; 0≤ x ≤ 0.15 were synthesized by a self-ignited sol-gel process. An annealing temperature of 950 °C is estimated via thermal-gravimetric (TGA) analysis. X-ray diffraction (XRD) scans have confirmed the formation of the ferrite phase with a spinel structure in all samples. Substitution of Ho ions on the B-site significantly reduced the porosity from 38 -to 23% and the crystallite size from 23.4 -to 21.7 nm. Microstructural analysis revealed a denser structure with an increase in Ho content. Dielectric results showed that both the dielectric loss and dielectric constant depict a nonlinear variation with the addition of Ho. Complex impedance behavior with a single semicircle for all samples suggests the predominant effect of the grain boundary mechanism. The substitution of Ho ions in place of Fe ions significantly decreased the electrical conductivity. The anisotropic Ho 3+ ions reinforce the L-S coupling which consequently enhanced the coercive force from 145 -to 389 Oe, and thus the anisotropy constant.